Penerapan Limbah Kotoran Sapi dan Kapur Kalsium Oksida (CaO) pada Pertumbuhan dan Produksi Tanaman Kacang Panjang (Vigna sinensis L.) - Rezki Fauzi; Tengku Boumedine Hamid Zulkifli; Koko Tampubolon; Irwan Agusnu Putra; Yunida Berliana; Dedi Kurniawan; Razali Razali; Octanina Sari Sijabat (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2020)
Introduction: The research was aimed to obtain an appropriate dose of cow manure waste, calcium oxide lime, and interactions in increasing the growth and yield of cowpea. Material and Methods: The research was conducted in Secanggang Village, Secanggang Subdistrict, Langkat District in June until September 2017. The research was conducted using the Randomized Block Design Factorial, the first factor (cow manure waste) dose of L0= 0 ton ha-1; L1= 10 ton ha-1; L2= 20 ton ha-1. The second factor (calcium oxide lime) dose of K0= 0 ton ha-1; K1= 3 ton ha-1; K2= 6 ton ha-1; and K3= 9 ton ha-1. Data were analyzed using the F and followed by DMRT at level 5% using IBM SPSS Statistics v.20 software. Results: The cow manure waste dosages of 10 until 20 ton.ha-1 significantly increased the plant height at 4 Weeks After Planting (WAP) and yield.plot-1 of cowpea ranged from 2.14 to 2.50% and 13.00 to 15.98%, respectively and the dose of 20 ton.ha-1 significantly increased the yield.sample-1 of 17.44% compared to untreated. The application of calcium oxide lime at the dose of 9 ton.ha-1 significantly increased the plant height of cowpea at 4 WAP of 2.46%, and the dose of 6 until 9 ton.ha-1 significantly increased the yield.sample-1 and yield.plot-1. However the highest was found in the dosage 6 ton.ha-1 of 13.51% and 20.16% compared to untreated. The interaction of cow manure waste with calcium oxide lime were not significant effect on growth and yield of cowpea.